PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, DUKUNGAN MANAJEMEN PUNCAK, DAN KEMAMPUAN PEMAKAI TERHADAP EFEKTIFITAS SISTEM INFORMASI AKUNTA (Studi Empiris pada kantor BPPKAD kabupaten Rembang) - Arum kamawati; Maslichah Maslichah; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
Computer-based accounting information system is essential applied in cooperatives to produce a form of financial statements information that is relevant and reliable. This study aims to demonstrate empirically the effect of the use of information technology, user participation, top management support and engineering capabilities users of accounting information systems at the effectiveness of accounting information systems. Sampling technique used is the census sampling technique (saturated sample) and get a sample of 80  samples. Questionnaires were returned and deserves to be treated as many as 80questionnaires. Data analysis technique used is the technique of linear regression analysis showed that the variables berganda.Hasil use of information technology, user participation, top management support, the ability of users of accounting information systems engineering positive influence on the effectiveness of the system of accounting informmasi. Keywords: Information Technology Utilization, User Participation, Top Management Support, Effectiveness SIA